PENGARUH BEBAN KERJA, KOMPENSASI DAN MOTIVASI INTRINSIK TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Murdapa, Purnama Andry (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2014)
This study aims to examine and analyze the effect of workload,compensation and intrinsic motivation on employee productivity (studies onPT. Bank Perkreditan Rakyat Agung Sejahtera Semarang).The method usedin this sampling technique is to use a census or a sample saturated. Thesample used in this study was 50 respondents who constitute the entirepopulation. The method of data analysis used is multiple linear regressionanalysis. The results of the t test, workload, compensation and intrinsicmotivation positive and significant impact on employee productivity. F testresults indicate that all the independent variables have a significant effecttehadap employee productivity. The coefficient of determination (R2) of 0.510which shows that 51% of employees' work productivity variable can beexplained by the independent variable workload, compensation and intrinsicmotivation, while the remaining 49 % is explained by other variables.